The Influence of Promotion Intensity on Brand Image Commercial Commodity Products Perum Bulog Divre Sulselbar In Makassar City - Dyah Rachma Wijayanti H.P; Abdul Razak Munir; Muhammad Ismail (SEIKO : Journal of Management & Business, 2023)
The Influence of Promotion Intensity on the Brand Image of Commercial Commodity Products of Perum BULOG Divre SulSelBar in Makassar City. This study aims to determine the Effect of Promotion Intensity on the Brand Image of Commercial Commodity Products of Perum BULOG Divre SulSelBar in Makassar City. The population is all partners / members of Perum BULOG assisted outlets who are actively listed as members of Sahabat Rumah Pangan KITA (RPK) located in the Makassar city area. The sample number is 150 members using Slovin's sample theory. Data analysis of this study used SPSS V.20, a data collection technique with questionnaire techniques, observation, documentation and literature review. The analysis techniques used are validity tests, reliability tests, inferential statistical tests and analysis. The results of this study are that the promotion intensityvariable (X) has a very strong relationship with the brand image variable (Y) and has a significant influence between the intensity variable s promosi (X) and brand image (Y) evidenced in the results of the correlation coefficient analysis with a significant value of 0.000 < 0.05 and the value of the coefficient of determination (R2) 0.645 or 64.5 percent which shows a very strong good. Keywords: Promotion Intensity and Brand Image